“Efecto de cuatro cosis de fertilizante organico enriquecido con microorganismos (ferti em) en el cultivo de ají pimentón (capsicum annuum L.) variedad california wonder, en el distrito de Lamas” - Villalobos Tantaleán, José Rolando (2015)
The effect of four doses of organic fertilizar enriched with microorganisms (ferti em) in growing pepper pepper (capsicum annuum 1) variety california wonder, in the district of Lamas, in order to determine the most effective dose of organic fertilizar was investigated enriched with microorganisms (Ferti EM) on the performance and profitability of growing pepper pepper ( Capsicum annuum L.) cv California Wonder conditions Lamas district. The complete block design was used with 5 treatments Random and 4 blocks, making a total of 20 experimental units. The treatments were 1000, 800, 600, 400 Kg.ha Ferti EM-1 and the control. were evaluated: Plant height (cm), number of flowers per plant (unit), number of fruits per plant (unit), fruit weight (g), fruit diameter (cm), along fruit {cm) and performance {{kg ha-1). With applications from 400-1000 kg ha-1 of Fari EM comparad to tha control, and high positiva correlation ratationships over the long fruit-linear responses were obtained, fruit weight and . Best results yield was 1000 kg ha-1 for Ferti EM (T4), with 21 338.72 kg ha-1 yield 185.7 g of fruít weight, 8.9 cm long with 7 79 cm fruit diameter and 5.16 fruits, B I C of 2.08; .. net profit of S I 9 950.32 Recommending applied dose of 1000 kg ha-1 of organic fertilízer Ferti EM in the cultivation of pepper pepper (Capsicum annuum L.) cv California Wonder conditions Lamas district. Keywords: organic fertilizer; ferti EM; Capsicum annuum; yield.